Synthesis gas production by the co-gasification of RDF-based pyrolysis char and tar - Sebe, Emese; Kállay, András Arnold (Multidiszciplinaris Tudomanyok, 2023)
We aimed to study the possibilities of synthesis gas production using char and tar originating from a Refuse-Derived Fuel (RDF) pyrolysis pilot plant. The main product of the thermal waste treatment plant is pyrolysis gas, while currently, the char is not utilized. During the pyrolysis process, a large amount of tar is also generated. Our goal was to find a more ecologically friendly alternative than landfilling in the case of both by-products. Steam gasification experiments were conducted at 900 °C in a small tubular reactor. The carbon conversion of the char-tar blend reached 95.3%.